The key features and practical applications of political technologies - Мовчан, Є. С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
In this article the process of technologizing of the socio- political sphere is described, the concept of political technologies is analyzed and it’s essential characteristics are highlighted. Particular emphasis has been placed on the analysis of the tendencies of using political technologies in modern political and administrative activities, and on their role in nation building. Political technologies were interpreted as a practice of political management and electoral process, informational and communicational technologies and as a certain models of social and political cooperation between authorities and public institutions.